I have two circles as: $C_1: (x-x_1)^2+(y-y_1)^2=r_1^2$ and $C_2: (x-x_2)^2+(y-y_2)^2 =r_2^2$ and these circles have non-empty intersection.

In other words $\sqrt{(x_1-x_2)^2+(y_1-y_2)^2}\leq r_1+r_2$.

Now I define a third circle as:

$C: (x-x_0)^2+(y-y_0)^2 = r_0^2$ where



$r_0=\sqrt{x_0^2+y_0^2-(x_1^2+y_1^2-r_1^2)(1-t)-(x_2^2+y_2^2-r_2^2)t}$ where $0\leq t \leq1$

Claim: C contains the intersection of $C_1$ and $C_2$ for all values of t such that $0 \leq t \leq 1$.

How can i prove this claim?

  • $\begingroup$ Your $r$ term seems a little weird. Two of the summands in there are $0$. And do you mean the centers of the circles are $(x_1,\ y_1)$ and $(x_2,\ y_2)$? As you have it, the two circles are centered at the origin and $x_i$ and $y_i$ are variables. $\endgroup$ – EuYu Oct 4 '12 at 18:53
  • $\begingroup$ You didn't address the issues I mentioned. It makes no difference if you're talking about circles or disks. Do you mean for the equation to hold for every $x_1,\ y_1,\ x_2,\ y_2$ satisfying the inequalities? $\endgroup$ – EuYu Oct 4 '12 at 19:10
  • $\begingroup$ just check now, sorry ;) $\endgroup$ – kotoll Oct 4 '12 at 19:11
  • $\begingroup$ To simplify the computation, you can, without loss of generality, assume that $(x_1,y_1)=(0,0)$ and $(x_2,y_2)=(1,0)$. $\endgroup$ – Aline Parreau Mar 31 '13 at 19:13

If point $(x_3,y_3)$ is in the intersection of $C_1$ and $C_2$ then $(x_3-x_1)^2+(y_3-y_1)^2=x_3^2+x_1^2-2x_3x_1+y_3^2+y_1^2-2y_3y_1 \leq r_1^2$ and $(x_3-x_2)^2+(y_3-y_2)^2=x_3^2+x_2^2-2x_3x_2+y_3^2+y_2^2-2y_3y_2\leq r_2^2$

Then the distance from $(x_0,y_0)$ is $\sqrt{(x_3-(1-t)x_1-tx_2)^2+(y_3-(1-t)y_1-ty_2)^2}=\sqrt{x_3^2+t^2x_2^2+(1-t)^2x_1^2-2(1-t)x_3x_1-2tx_3x_2+t(1-t)x_1x_2+y_3^2+t^2y_2^2+(1-t)^2y_1^2-2(1-t)y_3y_1-2ty_3y_2+t(1-t)y_1y_2}$ .

$\leq \sqrt{x_1^2(1-t)^2+x_2^2t^2+2x_1x_2t(1-t)+y_1^2(1-t)^2+y_2^2t^2+2y_1y_2t(1-t)-x_1^2-y_1^2+r_1^2+tx_1^2+ty_1^2-tr_1^2-tx_2^2-ty_2^2+tr_2^2}$

$\leq \sqrt{x_0^2+y_0^2-x_1^2-y_1^2+r_1^2+tx_1^2+ty_1^2-tr_1^2-tx_2^2-ty_2^2+tr_2^2}$

$= \sqrt{x_0^2+y_0^2-(x_1^2+y_1^2-r_1^2)(1-t)-(x_2^2+y_2^2-r_2^2)t}=r_0$

  • $\begingroup$ Could you please expand hidden steps between the line 2 and 3 for for the distance $\endgroup$ – kotoll Oct 9 '12 at 20:11

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.